Europejska integracja monetarna - doświadczenia Irlandii, Hiszpanii, Portugalii oraz Grecji - Kowalska, Magdalena (European monetary integration - cases of Ireland, Spain, Portugal and Greece, 2006)
The article presents the process of economic development of Ireland, Spain, Portugal and Greece. It describes also their experiences on the road to monetary integration with other countries of the euro zone. In the article, the course of nominal and real convergence in the analyzed countries is described, with the special focus on the form of public finance and inflation (together with Balassa-Samuelson effect). Moreover, the experience as regards participation in the ERM system, monetary policy implemented before the euro zone accession and the forecast of the future economic performance of these countries are presented. Attention is also paid to the recent events in Greece. The article is concluded with the observations about the regularities in the course of monetary integration of these countries. They can help the other European Union members which do not belong to the euro zone yet.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 38-60